Et fynsk krucifiks med slægtninge i Sønderjylland: Krucifikser fra begyndelsen af 1300-tallet - Wenningsted-Torgard, Susanne (Hikuin, 1999)
A crucifix on Funen with relations in southern Jutland By Susanne Wenningsted-Torgard During my work corcerning an analysis and grouping of all the crucifixes preserved in Denmark from the 14th century, a total of about 110 pieces, I realized that a small, fine exemplar in Roerslev Church on Funen is closely related with a group of crucifixes from the southern part of Jutland /North Schleswig, i.e. a crucifix in Randerup Church, one from St. Catherine Church in Ribe, one in Vester Nebel Church, and one of two pieces in Nørre Løgum Church. The figure in Randerup Church has earlier been related to one of two crucifixes in Gram Church, and according to a frontal view of the two sculptures the comparison seems reasonable. Yet, problems arise when one takes a side view of the figures, and through my investigation I have realized how important the profile of the figures is, not only for a stylistic analysis and classification but also for a judgement on the expressive character of the crucified Christ. In the Roerslev-Randerup-grouping the loin of the figures is or has been pushed backward towards the tree of the cross, the stomach is emaciated and hollow, the left shoulder is turned forward and the knees are bent.Through a view from the side we get a clear impression of a dead Christ, of a figure hanging heavily on the cross. The Gram crucifix, on the other hand, has an ‘optical’ swaying forward of the loin, whereby a rounded stomach protudes while the shoulders are pressed back.This results in a toand- fro movement contrary to the first group and also gives the impression of a rather vertical figure, of a Saviour still alive.